Habilidades cognitivas e o processo de aquisição da leitura: uma revisão sistemática da literatura brasileira - Mélo, Niedjá Sousa (2019)
The written code is a form of linguistic representation that implies the ability to understand ideas and concepts and transmit messages enabling the individual to interact with the literate world in which he is inserted. Reading is an instrument of social and cognitive formation of the subject, enabling him/her to be inserted in the culture. Thus, reading is a complex cognitive competence, to which an extensive variety of other skills and knowledge converge. The present study aimed to perform a survey of the academic production on the cognitive abilities involved in the learning process of reading from a systematic review of the profile of national research related to the theme and published between the years 2014 and 2018 in the Scientific Electronic Library Online (SciELO ). Of the 4,776 productions located in the initial search, 20 publications were selected to compose this research. The publications on cognitive skills associated with the process of acquisition of reading showed a decrease in production over the years analyzed. The decline of studies on the subject deserves attention of the scientific community, given the low results obtained by the country in international and national evaluations that measure the performance of Brazilian children in reading. In relation to the productions by Brazilian regions, the articles are mostly concentrated in the southeastern region of the country. The lack of longitudinal and experimental studies in the country also highlights the importance of developing research involving intervention and longitudinal monitoring programs, especially focusing on risk groups for reading difficulties. The analysis of the sample profile shows that few studies have investigated cognitive skills in the Early Childhood Education stage. This data is worrying, considering that the investigations in this school group would act as literary references for the educational work in kindergartens and preschools. The studies selected in this systematic review study investigated the acquisition of reading associated with different cognitive skills, namely: rapid serial appointment, phonological awareness, morphological awareness, syntactic awareness, metatextual awareness, auditory discrimination, visual processing, memory, body scheme/spatio- temporal orientation, reasoning, oral understanding, oral expression, decoding, phonological development and verbal fluency. The results found suggest that the acquisition of reading is eminently due to impairments in phonological skills.